A virulence factor as a therapeutic: the probiotic Enterococcus faecium SF68 arginine deiminase inhibits innate immune signaling pathways. (31st December 2022) - Ghazisaeedi, Fereshteh; Meens, Jochen; Hansche, Bianca; Maurischat, Sven; Schwerk, Peter; Goethe, Ralph; Wieler, Lothar H.; Fulde, Marcus; Tedin, Karsten
ABSTRACT: The probiotic bacterial strain Enterococcus faecium SF68 has been shown to alleviate symptoms of intestinal inflammation in human clinical trials and animal feed supplementation studies. To identify factors involved in immunomodulatory effects on host cells, E. faecium SF68 and other commensal and clinical Enterococcus isolates were screened using intestinal epithelial cell lines harboring reporter fusions for NF-κB and JNK(AP-1) activation to determine the responses of host cell innate immune signaling pathways when challenged with bacterial protein and cell components. Cell-free, whole-cell lysates of E. faecium SF68 showed a reversible, inhibitory effect on both NF-κB and JNK(AP-1) signaling pathway activation in intestinal epithelial cells and abrogated the response to bacterial and other Toll-like receptor (TLR) ligands. The inhibitory effect was species-specific, and was not observed for E. avium, E. gallinarum, or E. casseliflavus . Screening of protein fractions of E. faecium SF68 lysates yielded an active fraction containing a prominent protein identified as arginine deiminase (ADI). The E. faecium SF68 arcA gene encoding arginine deiminase was cloned and introduced into E. avium where it conferred the same NF-κ B inhibitory effects on intestinal epithelial cells as seen for E. faecium SF68. Our results indicate that the arginine deiminase of E. faecium SF68 is responsible for inhibition of host cell NF-κB and JNK(AP-1) pathway activation, and is likely to be responsible for the anti-inflammatory and immunomodulatory effects observed in prior clinical human and animal trials. The implications for the use of this probiotic strain for preventive and therapeutic purposes are discussed.